2000
DOI: 10.1002/(sici)1097-4601(2000)32:2<99::aid-kin5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for the reaction of OH radicals with some amino polycarboxylic acids

Abstract: Rate constants of OH radical reaction with some amino polycarboxylic acids (APCAs) such as EDTA, DTPA, HEDTA, NTA, and HIDA have been determined at different pHs using pulse radiolysis competition kinetics method with thiocyanate as the reference solute. The rate constants varied with pH (possibly due to their various pKs) and the plots of rate constants vs. pH are given. Rate constants for OH radical reaction with the various acid-base forms of these amino polycarboxylic acids are estimated from the plateau v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…under acidic conditions (see details that are provided in the Supplementary Material). The kinetics of EDTA reacting with hydroxyl radical, •OH, is also pH-dependent with a reported second-order reaction rate constant at pH 4 of k 4 = 4×10 8 M -1 s -1 , k 5 = 2×10 9 M -1 s -1 at pH=9, and k 6 = 5.7×10 9 M -1 s -1 at pH=11[40,41]. A faster hydroxyl radical rate at high pH is consistent with our current observations.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…under acidic conditions (see details that are provided in the Supplementary Material). The kinetics of EDTA reacting with hydroxyl radical, •OH, is also pH-dependent with a reported second-order reaction rate constant at pH 4 of k 4 = 4×10 8 M -1 s -1 , k 5 = 2×10 9 M -1 s -1 at pH=9, and k 6 = 5.7×10 9 M -1 s -1 at pH=11[40,41]. A faster hydroxyl radical rate at high pH is consistent with our current observations.…”
supporting
confidence: 91%
“…HEDTA, in contrast is slightly more effective in promoting the photolytic decomposition of PFOS than EDTA as shown in Fig. 8 8.2×10 9 M -1 s -1 , pH=11) is slightly higher than that of •OH reacting with EDTA (k 6 = 5.7×10 9 M -1 s -1 , pH=11) [41]. The amines and the methylenes play a crucial role in promoting PFOS photodegradation, which allow for an effective attack by •OH via Hatom abstraction from an amine or from a methylene.…”
Section: Degradation Of Pfos Pfhxs and Pfbsmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, it should be noted that chelate DTPA could be degraded by • OH or direct UV photolysis, reducing its chelation capacity with metals in the system. , However, we concluded that in our system, DTPA was not subjected to any degradation during the O 2 •– generation phase ( i.e., first 30 s of UV 254 irradiation), which was evidenced by monitoring its absorption peak . In addition, the concentration of FA is 3 orders of magnitude larger than that of DTPA and the reactivity of • OH is similar to either FA or DTPA, , ensuring that DTPA will not be consumed by • OH.…”
Section: Methodsmentioning
confidence: 72%
“…•− generation phase (i.e., first 30 s of UV 254 irradiation), which was evidenced by monitoring its absorption peak. 31 In addition, the concentration of FA is 3 orders of magnitude larger than that of DTPA and the reactivity of • OH is similar to either FA or DTPA, 34,49 ensuring that DTPA will not be consumed by • OH.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%